A Further Study and Assessment on Geographic Information System: From Highway Ecological Landscape Environment Angle of View. (28th June 2022) - Zhou, Ling; Liu, Weijie
Abstract : With the development of the national economy, our country's highway construction is developing in a more advanced and humane direction. On the basis of meeting traffic needs, people have begun to pay more attention to the construction of highway landscapes. Based on the understanding and integration of domestic and foreign landscape evaluation system research, this paper constructs a new type of highway landscape evaluation model and selects Zhangjiakou, one of the co-host cities of the Winter Olympics, to analyze and verify the model. We use the designed evaluation model to analyze and evaluate the three highways in the Zhangjiakou area. First, based on the analytic hierarchy process, the combination of qualitative and quantitative evaluation indicators is selected, and then, the GIS geographic information system is used to obtain the basic data of the quantitative indicators and the questionnaire method is used. The grade evaluation of three highways is realized, and the optimization measures and construction strategies for the landscape quality along the highway are proposed. The results show that the research results of this evaluation system are of great significance to the landscape construction along the line, the protection of landscape resources, and the development of tourist roads.